Spectrophotometric Determination of Famotidine by Cresol Red with Charge-Transfer Reaction - Liu, Ying-Hong; Ma, Wei-Xing; Li, Yan-Hui (Asian Journal of Chemistry, 2010)
A new spectrophotometric method for the determination of famotidine was carried out. The dependence of the absorbance on solvents, temperature and reaction time was investigated. In ethanolic medium famotidine reacted with cresol red to form a 1:2 charge-transfer complex with the absorbance decreased obviously at 520 nm. The decrease value of the absorbance (DA), due to the presence of famotidine was correlated with its concentration. Linear relationship with good correlation coefficient (0.9995) was found between DA and the concentration of famotidine in a concentration range of 2-61 μg mL-1. The assay limit of determination was 0.28 μg mL-1. The proposed method was successfully applied to the determination of the investigated drug in tablets and capsules with the recoveries of 98.0 and 99.5 %, respectively.